Self Efficacy: A View from Junior High School Students and Its Gender Interaction - Marlinda Mulu; Priska Filomena Iku; Fransiskus Laka Lazar; Mariana Jediut (Universitas Negeri Makassar, 2023)
Self-efficacy is an essential factor in the learning process of a student. Self-efficacy is the belief in their skills to complete tasks or achieve targets. Many studies on self-efficacy have been carried out, but there are still few that examine the self-efficacy of junior high school students and how gender influences it. Therefore, it is crucial to examine the self-efficacy of junior high school students and investigate differences in student self-efficacy by gender. Data were collected from research respondents of 168 students, with 95 female and 73 male students. This research adopted a quantitative design as data were collected from questionnaires. Results show that in general students' self-efficacy is in the high category. In addition, students' self-efficacy in terms of gender, male and female students both have high self-efficacy.Furthermore, the results of the ANOVA test showed that there was a significant difference between the self-efficacy of female and male students. The average self-efficacy of female students is higher than male students. Studies show that even though male and female students have high self-efficacy, there are still students who have low or even very low self-efficacy. Therefore, it is highly recommended that schools provide bombing and counseling services for these students.